Peningkatan Pengetahuan Dan Praktik Ibu Balita Tentang Komposisi Dan Informasi Nilai Gizi Makanan Kemasanan - Marlina, Paramitha Wirdani Ningsih; Rasmada, Sada; Wulandari, Agnes Maharani Puji; Miensugandhi, Aloysius Prima Cahya; Dampang, Damelya Patricksia; Jati, Mateus Bagas Nugroho (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
Public awareness and ability to read food labels is still very low. A National Consumer Protection Agency survey stated that 6.7% of people in Indonesia pay attention to the completeness of food labels. One of the Messages of Balanced Nutrition is reading food labels. S1 Nutrition Study Program STIK Sint Carolus together with Nutritionists from the Galur Supporting Community Health Center provided counseling to mothers of toddlers on the topic "Let's Check the Coins (Composition and Nutritional Value Information) on Food Packaging" to 20 mothers of toddlers who visited the Posyandu. Counseling participants are given an identity and pretest form to fill out. The first session included material on definitions and food labels, and the second session provided material on how to read composition and nutritional value information. The third session involved practicing reading packaged food and conducting questions and answers and filling in the posttest form. After 3 days of providing material, monitoring and evaluation was carried out via Whatsapp. Based on the results of statistical analysis, 55% of mothers were classified as lacking knowledge during the pretest. However, it increased after nutrition education was carried out to 95% of mothers who were classified as well informed. The results of the Wilcoxon analysis show that there is a difference in knowledge between before and after counseling with p-value = 0.007. The results of monitoring and evaluation from 5 mothers, 100% of mothers had paid attention to food labels on packaging, especially composition and nutritional information. There has been a change in practice in reading food labels. Keywords: food labels; knowledge; nutrition information; nutrition counseling